Improvement of Technological Modernization Using Behavioral Economics - KUSSAINOVA, Ademi; RAKHIMBERDINOVA, Madina; DENISSOVA, Oxana; TASPENOVA, Gauhar; KONYRBEKOV, Medet (Journal of Environmental Management and Tourism; Vol 9 No 7 (2018): JEMT Volume IX Issues 7(31) Winter 2018, 2019)
The purpose of this publication is to explain the applying of behavioral economics tools in the process of the technological upgrading of the Republic of Kazakhstan to be implemented. We need to: define the concept of behavioral economics; to reveal and describe in what way tools of behavioral economics may be applied, their nature and impact in the process of technological upgrading on the types of management; to understand and explain three principles of decision-making, the algorithm to make choice by people, profitable and unprofitable choices. Two main types of a feedback are provided and explained: reinforcing and balancing feedback. In this article, it is required to find out what solutions are necessary for a post-industrial economy, what is constituted by methodological tools, which are required to implement the accelerated technological upgrading, and the subjects of organizational support of technological change.